“Empty Book” as Kind of Extremely Small Texts - I. S. Samokhin; N. L. Sokolova; M. G. Sergeyeva; N. V. Nikashina (Научный диалог)
Extremely small texts presented in the format of “empty book” (or “blank book”) are considered. The authors of the article extend this concept to any book consisting of a title and blank pages as the main text. The relevance of the study is a significant increase in the popularity of the studied literary form, which is observed in the 2010s (primarily in the United States). It is noted that the concept of “empty book” should not be confused with the concept of “novel without words” (“wordless novel,” “novel in woodcuts”), as the latter case refers to the fiction genre, according to the laws of which the development of the plot is transmitted not by language, but by graphic means: with the help of illustrations. The review of “empty books” is made in the framework of the classification of extremely small texts proposed by A. Kondratov (according to which they are of two types: “null” and “void”). The authors come to the conclusion that all the texts are “empty,” that is, their non-verbal nature is the “equivalent of verbal signs.” It is emphasized that the American “empty books” can not be attributed to fiction, even with a large share of conditionality, because their titles are built on the model used in works of another kind - in those that are written at the junction of popular science and journalistic discourses.